The Effect Of Corn On Pastry Quality - Safina, Dinara; Faridah, Anni; Andriani, Cici; Anggraini, Ezi (Universitas Negeri Padang, 2024)
High imports of wheat and increasing consumption of wheat as the main raw material for the Bakery, Pastry,Pasta and Noodle industries. Pastry is a type of product without yeast that has a dry and layered texture. To in-crease nutritional value, add variety to pastry and reduce the use of wheat flour, corn can be used as a substitute.Corn production in West Sumatra increases every year and the price is relatively cheap because it is underutilized by the community. This research aims to analyze the effect of 0%, 20%, 30% and 40% corn on pastry quality. Thistype of pure experimental research uses a completely randomized design (CRD) method and three repetitions. The data collection technique was carried out by giving a questionnaire to three limited panelists who were lecturers in the Pastry and Bakery course, Family Welfare Science, Culinary Management concentration, UNP, with primary data types. Data were analyzed using ANOVA, if Fcount > Ftable then continued with the Duncan Test. The results of the research showed that the average value was almost the same for each treatment, except for the color, flakyand sweet taste quality tests for corn. This is proven by the ANOVA results, where the color quality, flaky texture and sweet taste of the corn are different. The best pastry quality value is when corn is used as much as 30%.